Detection of lipoarabinomannan in urine and serum of HIV-positive and HIV-negative TB suspects using an improved capture-enzyme linked immuno absorbent assay and gas chromatography/mass spectrometry. (July 2018) - Amin, Anita G.; De, Prithwiraj; Spencer, John S.; Brennan, Patrick J.; Daum, Joshua; Andre, Barbara G.; Joe, Maju; Bai, Yu; Laurentius, Lars; Porter, Marc D.; Honnen, William J.; Choudhary, Alok; et al.
Abstract: TB diagnosis and treatment monitoring in resource limited regions rely heavily on serial sputum smear microscopy and bacterial culture. These microbiological methods are time-consuming, expensive and lack adequate sensitivity. The WHO states that improved TB diagnosis and treatment is imperative to achieve an end to the TB epidemic by 2030. Commercially available lipoarabinomannan (LAM) detection tools perform at low sensitivity that are highly dependent on the underlying immunological status of the patient; those with advanced HIV infection perform well. In this study, we have applied two novel strategies towards the sensitive diagnosis of TB infection based on LAM: Capture ELISA to detect LAM in paired urine and serum samples using murine and human monoclonal antibodies, essentially relying on LAM as an 'immuno-marker'; and, secondly, detection of α-d -arabinofuranose and tuberculostearic acid (TBSA)- 'chemical-markers' unique to mycobacterial cell wall polysaccharides/lipoglycans by our recently developed gas chromatography/mass spectrometry (GC/MS) method. Blinded urine specimens, with microbiologically confirmed active pulmonary TB or non TB (HIV+/HIV–) were tested by the aforementioned assays. LAM in patient urine was detected in a concentration range of 3–28 ng/mL based on GC/MS detection of the two LAM-surrogates, d -arabinose and tuberculostearic acid (TBSA) correctly classifying TB status with sensitivity > 99% and specificity = 84%. The ELISA assay had high sensitivity (98%) and specificity (92%) and the results were in agreement with GC/MS analysis. Both tests performed well in their present form particularly for HIV-negative/TB-positive urine samples. Among the HIV+/TB+ samples, 52% were found to have >10 ng/mL urinary LAM. The detected amounts of LAM present in the urine samples also appears to be associated with the gradation of the sputum smear, linking elevated LAM levels with higher mycobacterial burden (odds ratio = 1.08–1.43; p = 0.002). In this small set, ELISA was also applied to parallel serum samples confirming that serum could be an additional reservoir for developing a LAM-based immunoassay for diagnosis of TB.